PERSPEKTIF MUHAMMAD ‘ABDUH DALAM PEMBAHARUAN PENDIDIKAN ISLAM - Yogi Fernando; Nunu Burhanuddin (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The science of education always develops with the times. Therefore, the education system must be changed. Describing the results of the study, the researcher offers Muhammad "Abduh's" perspective to overcome the problem by reforming Islamic education to reduce the differences between the two education systems. A proper and progressive attitude is to change the purpose of education to suit the times. In connection with the teachings of the Prophet of Allah, Islamic education today must harmonize the science of the world and the Hereafter. By working together, both parties can produce cadres who based on divine values can find and solve world problems. The right attitude is to update educational goals to adjust to the times, because each solution will be outdated and require new solutions.